2002
DOI: 10.1002/ptr.1025
|View full text |Cite
|
Sign up to set email alerts
|

Antimalarial activity of extracts and alkaloids isolated from six plants used in traditional medicine in Mali and Sao Tome

Abstract: Methanol and chloroform extracts were prepared from various parts of four plants collected in Mali: Guiera senegalensis (Gmel.) Combretaceae, Feretia apodanthera (Del.) Rubiaceae, Combretum micranthum (Don.) Combretaceae, Securidaca longepedunculata (Fres.) Polygalaceae and two plants -collected in Sao Tome: Pycnanthus angolensis (Welw.) Myristicaceae and Morinda citrifolia (Benth.) Rubiaceae were assessed for their in vitro antimalarial activity and their cytotoxic effects on human monocytes (THP1 cells) by f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
81
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(83 citation statements)
references
References 9 publications
1
81
0
1
Order By: Relevance
“…Furthermore, the methanol and chloroform extracts of the root exhibited an IC 50 of ˃250 µg/ml against the chloroquinone resistant P. falciparum strain (Ancolio et al, 2002). Elsewhere, extracts from seeds of S. longipedunculata did not show any activity at 50 µg/ml against P. falciparum FCA-2 from Ethiopia (Kassa et al, 1998), suggesting that the antimalarial compounds may only be present in the leaves and roots.…”
Section: Antiplasmodial Activitymentioning
confidence: 97%
“…Furthermore, the methanol and chloroform extracts of the root exhibited an IC 50 of ˃250 µg/ml against the chloroquinone resistant P. falciparum strain (Ancolio et al, 2002). Elsewhere, extracts from seeds of S. longipedunculata did not show any activity at 50 µg/ml against P. falciparum FCA-2 from Ethiopia (Kassa et al, 1998), suggesting that the antimalarial compounds may only be present in the leaves and roots.…”
Section: Antiplasmodial Activitymentioning
confidence: 97%
“…Although oxidative stress may have little or no role to play in the etiology of these diseases, except in gastrointestinal disorders such as ulcer, the strong antioxidant potential of this plant suggests that it is plausible it may exert therapeutic efficacy in oxidativestress related diseases for which it is not currently recognized. This strong antioxidant activity is consistent with its phytochemical constituents which include alkaloids (Ancolio et al, 2002), guirenone and other polyphenols (Silva, Gomes, 2003;Le Grand, 1989). In fact, Bucar et al (1989) isolated 5-methylflavesperone and rhamnetin from Guiera senegalensis and demonstrated that while rhamnetin strongly inhibited peroxidation of phospholipids liposomes, the former possessed little or no such activity.…”
Section: Discussionmentioning
confidence: 53%
“…Guiera senegalensis is reportedly useful in the treatment of malaria (Ancolio et al,2002), fungal diseases (Silva, Gomes, 2003) and snake bite (Abubakar et al, 2000), while in Northern Nigeria, the plant is also reported to be useful in the treatment of gastrointestinal disorders and skin diseases. Although oxidative stress may have little or no role to play in the etiology of these diseases, except in gastrointestinal disorders such as ulcer, the strong antioxidant potential of this plant suggests that it is plausible it may exert therapeutic efficacy in oxidativestress related diseases for which it is not currently recognized.…”
Section: Discussionmentioning
confidence: 99%
“…It possesses tonic, diuretic, antidiarrhea, antibiotic, antigonorrheal, antirheumatic and vermifuge (4,5,6). The leaves in decoction and chewed fresh leaves are used to treat coughs, bronchitis, hepatobiliary diseases, hepatitis and malaria (7). In combination with other plants, the leaves of Kinkeliba treat gonorrhea.…”
Section: Introductionmentioning
confidence: 99%